Pedagogical communication and academic achievement (Journal of Human Sciences, 2023)
This research paper intends to investigate the impact of pedagogical communication on academic achievement. In the fields of Education and Didactics, communication is the compass that leads the teacher to choose the most appropriate strategies to assess various situations that might hinder learners’ understanding and thus their progress in the learning process.Not only are these assessment strategies not limited to presenting relatively less complex situation problems, but they also require the employment of new terms that are more meaningful to learners and are in the range of their linguistic ability.Researching pedagogical communication derives its legitimacy from our keenness to contribute to achieving a number of long-term goals, which seek to change the position of the learner within the educational institution to become an active participant in the educational process because it is no longer sufficient for the individual to have high cognitive competencies and mental abilities in order to succeed in learning and solving problems easily and effectively.